Relación entre las estrategias de enseñanza y la formación del pensamiento crítico frente a la problemática medio ambiental de los alumnos del 2do grado de secundaria en las I.E del distrito de Nueva Cajamarca - Mera Tantalean, Alex (2013)
The research was planned and executed in the second grade level of educational institutions at the secondary level Nueva Cajamarca district in order to verify the link between two variables, one as part of the teaching, management strategies related to teaching training of critica! thinking, the other variable as part of the intellectual formation of students, the same critica! thinking as an achievement but focused on environmental issues as central to our scientific occupation as teachers motivated by the plight of ecology in the globe. Our work is supported by a theoretical framework that describes and interprets the process of human thought from a comprehensive dimensional sphere encompassing not only its fundamental characteristics, but also the essential skills involved in their activation and use, typical of an efficient level to consolidate the features that make up the profile of a great thinker, we put these concepts and these Nariables in the context of the school setting and the same act of teachingleaming proposed and implemented by the teacher through a variety of strategies and process by students and students through the manifestation of a number of cognitive and intellectual positions. Our objective. was to describe the possible association between the use of teaching strategies that handles the management of leaming in training linked to critica! thinking in second graders three secondary level educational institutions in the district of Nueva Cajamarca: Manuel Fidencio Hidalgo Flores, Los Olivos and Monterey, of which 65 students were taken in the first institution to 39 students in the second and 38 students in the third, so we had a total of 142 students and members of the population. In the group of teachers to integrate reach an amount 6 The research was adjusted to a descriptiva correlational design, with the instrumental supports for the teacher questionnaire and a test for students, both instruments were applied once, which product might get results that allowed us to test our hypothesis research in the sense that the teaching strategies of critica! thinking training in educational institutions Secondary Level Nueva Cajamarca district, have a weak positiva relationship (0.20), with a calculated value of Pearson's r (two , 4968) slightly higher than the tabular value ( 1. 645).